A novel dry powder extinguishant with high cooling performance for suppressing lithium ion battery fires. (February 2023) - Li, Xiutao; Zhang, Mengjie; Zhou, Zhenyang; Zhu, Yuxian; Du, Kang; Zhou, Xiaomeng
Abstract: Fighting lithium ion battery (LIB) fire has always been a hard work, due to the uncontrollable internal thermal runaway (TR) reactions of LIBs. In this work, a kind of inorganic phase change material composited commercial dry power extinguishant was studied for LIB fire. Different with the traditional dry powder extinguishants, the composite dry powers exhibited large heat absorbing capacities below the TR temperatures of LIBs. The results of LIB TR propagation suppression experiment show that the composite dry powers not only can extinguish LIB fire, but also can suppress LIB TR propagation. Moreover, the composite dry powers still keep the advantages of low cost, insulation and environment friendliness. This work delivers a novel method for designing more practical dry power extinguishants to suppress LIB fires.